The Relationship between Visual-Evoked Potential and Optic Coherence Tomography and Clinical Findings in Parkinson Patients. (23rd February 2023) - Tuncer, Zeynep; Dereli Can, Gamze; Dönmez Keklikoğlu, Hava; Eren, Fatma Ayşen; Yülek, Fatma; Deniz, Orhan
Abstract : Background . In Parkinson's disease (PD), dopamine deficiency is present not only in the nigrostriatal pathway but also in the retinal and visual pathways. Optic coherence tomography (OCT) can be used as morphological evidence of visual influence from early nonmotor symptoms. The aim of this study was to investigate the relationship of OCT and visual evoked potentials (VEPs) of eyes with the severity of clinical findings and ocular findings in PD. Methods . A group of 42 patients diagnosed with idiopathic PD and a control group of 29 people between the ages of 45–85 were included in our study. VEP was recorded in the patient and control groups. OCT measurement was made with the Optovue spectral-domain device. Foveal thickness and macular volume were measured in the foveal region and in the parafoveal and perifoveal regions in the temporal, superior, nasal, and inferior quadrants. RNFL (retinal nerve fiber layer) was measured in temporal, superior, nasal, and inferior quadrants. Ganglion cell complex (GCC) was evaluated in the superior and inferior quadrants. Using the UPDRS clinical scale, the relationship between measurements and the differences between the control group and the patient group were evaluated. Results . Among the OCT values in our study, foveal, parafoveal, perifoveal thickness, macular volume, RNFL, and GCC measurements were performed for the right and left eyes, and no difference was found between the patient group and the control group. There was no difference in VEP amplitude and latency values between the patient and control groups. The relationships between UPDRS and modified Hoehn Yahr staging and OCT and VEP measurements in the patient revealed no correlation. Conclusions . Studies on whether OCT measurements can functionally be a marker or which segments are more valuable for disease progression in patients with PD are needed. Visual dysfunction in PD cannot be attributed only to retinal pathology; however, the retina may provide monitoring of the status of dopaminergic neurodegeneration and axonal loss in PD.